Understanding Strategy Implementation: Progress along Performance of Meru County Government in Kenya - Ntoiti, Kelvin Mutuma; Makau, Stephen Muathe (European Scientific Journal, ESJ, 2022)
Below-average performance is a characteristic that has been common to many county governments in Kenya. The counties, formulate a County Integrated Development Plan as a guiding roadmap for five years. Besides the well-formulated strategies in Meru County, performance and effective service delivery have not been satisfactorily achieved. This study was designed to investigate the strategy implementation and performance of the Meru County Government. The study’s specific objectives were; to determine the effects of resource allocation, organizational culture, leadership, and organizational structure on strategy implementation and performance of Meru County Government. The variables of the study were measured using their respective indicators as follows. Resource allocation; finance and human resources. Organizational culture; values and goals. Leadership; style and leaders’ experience. Organizational structure; degree of decentralization. Performance; service delivery and county infrastructural development. Data was collected using a questionnaire with a Likert scale type of questions. The study targeted 291 employees of Meru County Government and a descriptive research design was used. Multiple regression analysis was used to analyze data. Findings indicated that the above-outlined variables had a positive and significant influence on the county government’s performance. The study among others recommends that; the county government should allocate adequate resources for the execution of its strategies, and to improve organizational leadership, the management should have more employees contribute to decision-making and periodic workshops and/or training should be held for all staff. On organizational structure; promoting interdepartmental learning and creating a short chain of command can help transform performance for the better.